FENOMENA PENGGUNAAN CHATGPT DALAM PRAKTIK PENDIDIKAN : ANTARA SISI POSITIF DAN NEGATIF - Arumsari, Diajeng (Jurnal Pendidikan Sosiologi Undiksha, 2024)
The world is now being faced with technological advances that are very influential in today's life. GPT Chat is one example of technological advancement, especially in the field of education. The purpose of this study is to describe the positive and negative impacts resulting from the use of GPT Chat in educational practice. The research method used is literature review analysis. The results found that there are two impacts related to the use of GPT Chat in educational practice. The positive impact is being an effective and affordable learning tool, providing benefits in writing scientific papers, providing additional information that is up to date, can help the process of preparing final assignments or theses. The negative impact is the decline in cognitive ability to reason critically, become dependent on technology, do not always produce the right answer, reduce creativity. The conclusion of this research is that the emergence of artificial intelligence such as ChatGPT (Generative Pre-Trained Transformer) brings new innovations in the world of technology, especially in the field of education. The capabilities offered by ChatGPT make an educational challenge for educators and students in the learning process by providing positive and negative impacts.